2021
DOI: 10.1007/s11259-021-09845-9
|View full text |Cite
|
Sign up to set email alerts
|

Milk composition, fatty acids profile and fat globule size of bottlenose dolphin (Tursiops truncatus, Montagu 1821) milk at early lactation

Abstract: Research data on milk composition in cetaceans are scattered and fragmentary. This paper analyses the gross and mineral composition, the fatty acids profile and the fat globule size of bottlenose dolphin ( Tursiops truncatus ) colostrum and milk at early lactation. The milk samplings were carried out on three lactating female of bottlenose dolphins at the 1st, 4-5 and 20-42 day post partum. High percentages of dry matter (51.88%), fat (26.08%) and protein (13.83%) were found in the colostrum on the first day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…However, the transfer of contaminants is particularly effective during lactation as the milk of these marine mammals is very rich in lipids dispersed in the form of droplets (milk fat globules) and packed into a membrane inherited from the mammary gland [116]. In a recent study [117], it was found that in bottlenose dolphin milk there is an average of 20.57% of lipids; the study also highlighted the abundance of unsaturated fatty acids (Unsaturated Fatty Acids/Saturated Fatty Acids ratio = 2.64). However, it should not be forgotten that the composition of fatty acids in milk is linked to food intake and mobilization from fat (blubber) deposits [118].…”
Section: Discussionmentioning
confidence: 99%
“…However, the transfer of contaminants is particularly effective during lactation as the milk of these marine mammals is very rich in lipids dispersed in the form of droplets (milk fat globules) and packed into a membrane inherited from the mammary gland [116]. In a recent study [117], it was found that in bottlenose dolphin milk there is an average of 20.57% of lipids; the study also highlighted the abundance of unsaturated fatty acids (Unsaturated Fatty Acids/Saturated Fatty Acids ratio = 2.64). However, it should not be forgotten that the composition of fatty acids in milk is linked to food intake and mobilization from fat (blubber) deposits [118].…”
Section: Discussionmentioning
confidence: 99%